Adaptive strategies and thermal perceptions in intermittently used congregational Spaces: A case study - Gemici, Zafer; Dogan, Ahmet (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2024)
In spaces with considerable volumes that are sporadically used and typically not operating at full capacity, existing thermal comfort models face limitations. This research aims to reveal disparities between these models and survey-based comfort assessments. Comfort calculations were conducted using conventional thermal comfort models based on measured parameters and compared with survey data. Notable differences prompted the formulation of a more robust correlation, accounting for 83.4 % of the variations in Predicted Mean Votes (PMV). A regression model derived from survey data shows a high coefficient of determination (R-2 = 0.84), supporting its applicability for large intermittently used spaces like mosques. Addressing limitations of existing models, this research introduces a practical and simplified approach to predicting thermal comfort, enhancing assessments in these distinctive spaces. The study also examines mosque indoor air quality dynamics. Despite sporadic ventilation, CO2 levels rose from 1500 ppm to 2500 ppm during Friday prayers, posing potential health risks. Before prayers, indoor CO2 and humidity met ASHRAE Standard 62, ISO 7730, and EN15231 values. To mitigate health concerns from elevated CO2 levels, improved ventilation systems are necessary. Comfort temperatures were only achieved during prayer periods.
Keywords: Thermal comfort; Intermittently used space; Indoor air quality; Survey study; Adaptive response; REDUCED ENERGY-CONSUMPTION; OPERATIONAL STRATEGIES; COMFORT; MODEL; MOSQUES; OCCUPANCY; THEATER; Engineering